Efek Kedelai Terhadap Faal Ginjal Diabetes Melitus: Effects of Soybean on Kidney Function in Diabetes Mellitus - Putri Dafriani (NERS Jurnal Keperawatan, 2011)
Diabetes mellitus is a metabolism disease associated with a number of microvascular (retinopathy, neuropathy and nephropathy) and macrovascular (ischemic heart disease, cerebrovascular disease and peripheral vascular diseases) complications. Soybeans have been consumed for a long time as an important protein source to complement grain protein soybean contain various nutritious and functional components such as isoflavonoids, which are beneficial against stress oxidative. This study aimed to explain soybean effect to nephropathy diabetic. Soybean have some advantages like isoflavonoids, protein, fiber, and fitoestrogen. All of advantages are used to eliminate diabetic complication.